Effect of Addition of Plastic Fibres on Strength Characteristics of a Subgrade Soil - Kaushal, AShutosh (My University, 2019)
In today’s time, plastic materials (which otherwise pose great threat to environment), can be alternatively and smartly utilized in civil engineering as a soil stabilizing material (apart from the more traditional cement and lime) to achieve economy and reduce waste impact on environment. In present study,effect of addition of plastic Fibres (shredded wrappers) on the strength characteristics of flexible pavements have been studied. Available literature has been reviewed, and then experiments were performed to compute the liquid limit, plastic limit and plasticity index of soil to categorize type of soil. OMC and MDD were computed at various plastic contents (by % of dry weight of soil). The CBR test has been performed at different percentage plastic contents. The maximum value of CBR was obtained as 4.01% at 1.5% plastic content. The design of pavement section was carried out done for different traffic volumes to find the most efficient and economical traffic condition for which this method could be most advantageous. Thickness of pavement for each layer (as per CBR corresponding to 0% and 1.5% plastic content) was determined using IRC-37:2018 design plates. The theoretical values of vertical compressive and horizontal tensile strains at critical locations has been determined. The theoretical value of modulus of elasticity (with 0 % and 1.5 % optimum plastic addition) ware calculated using IRC 37:2018. Trial sections filled with virgin soil and reinforced soil at various percentages of waste plastic content were compacted manually to 250 mm thickness and the subgrade modulus were calculated experimentally by using a Light Weight Deflectometer. The theoretical and experimental modulus values were compared, and the most optimized pavement thickness has been designed with IIT PAVE.
Keywords: Plastic Fibre; Flexible Pavement; CBR; LWD